Cashew cultivation in Guinea-Bissau – risks and challenges of the success of a cash crop (Scientia Agricola, 2015)
In recent decades a boom in cashew (Anacardium occidentale)cultivation has taken place in Guinea-Bissau, leading to the replacement of traditional slash-and-burn agriculture by a cash crop. As a result, the country is currently one of the world’s largest producers of raw cashew nuts and the cashew sector has acquired enormous importance in Guinea-Bissau’s economy. Changes induced by the cashew boom at social and environmental levels are yet to be analyzed and understood. The present study provides an account of the process of cashew expansion in Guinea-Bissau, reviews the current situation and discusses its future prospects. The cashew tree was introduced into the country by the Portuguese in the XIXth century, but only effectively expanded in the mid-1980s. It is largely cultivated by small farmers around villages and also plays a role in land ownership, since land tenure practices are linked to the planting of trees. The effects of this cashew boom on habitat fragmentation, fire regimes and biodiversity are still to be assessed. On the other hand, the spread of pests and diseases is becoming a problem. Strong dependence on a single cash crop also renders the country vulnerable to market fluctuations, entailing risks to local producers and the national economy. In the medium term, losses of export earnings can occur, which may impact the living standards and food security of Bissau-Guineans both in urban and rural areas.